Acute Traumatic Isolated Trapeziometacarpal Joint Subluxation: A Case Report and Literature Review - Kastanis G; Siligardou M.R.; Tsioupros A; Chaniotakis C; Pantouvaki A; Kapsetakis P; Ktistakis I; Stavrakakis I (Medical Science: Trends and Innovations Vol. 12, 2025)
The trapeziometacarpal joint (TMCJ) is a biconcave–convex saddle joint that is composed of the first metacarpal bone (1st MC_ and the trapezium. It allows a wide range of motion and multidirectional movement of the thumb. TMCJ of the thumb is an unstable joint anatomically and depends on the integrity and normal functionality of the ligaments to prevent dislocation. Dislocation or subluxation of the trapezio-metacarpal joint generally appears more often as injuries accompanied by intraarticular fracture of the base of the first metacarpal or trapezium. Isolated dorsolateral subluxation of the trapeziometacarpal joint appears more often with osteoarthritis of the joint rather than as a traumatic lesion and is an unstable injury because the ligaments of the joint present some degree of impairment. Suspicions to diagnose the injury and precocious therapeutic management avoid complications, which lead to impairment of hand function quality. Therapeutic procedures for TMCJ dislocation are controversial in the literature. The aim of this study is to present a case of a 28 year-old man, who after a direct impact with a heavy object (hummer) over the base of the thumb, presented in the emergency department with an anterolateral subluxation of trapeziometacarpal joint and based on this case, to recall the modalities of the adequate treatment of the respective injury in literature. The patients reported pain on the base of the TMCJ, especially during motion of the thumb and swelling. Clinical examination revealed a painful trapeziometacarpal joint during range of motion and signs of partial instability. It was decided on an open treatment with scope to examine the capsuloligamentous complex of the trapeziometacarpal joint. Passive exercises and manual therapy were performed initially to increase soft tissue flexibility and the range of motion. Mobilization enhances the earlier recovery of mobility and return to the previous level of daily activities. Isolated traumatic trapeziometacarpal dislocation or subluxation is a very uncommon lesion that can be missed in the emergency department, so the physician must be suspicious of such a species of injury.